Are The Egyptian Travel Agencies Learning Organizations? - Fatma Zohra Talhi; Bassam Samir Alromeedy (My University, 2019)
Learning organization characteristics supports travel agencies to keep up with constant changes in tourism labor market. Also, learning organization characteristics help travel agencies achieve the sustainable competitive advantage. The study focused on answering the question: To what extent the Egyptian travel agencies have the characteristics of the learning organizations? Out of 250 questionnaires distributed on a random sample of employees in travel agencies – category A in greater Cairo, 216 have been retrieved and found usable for analysis. The study proved that the Egyptian travel agencies – category A in greater Cairo have the learning organizations' characteristics. Therefore, Egyptian travel agencies – category A are considered learning organizations. Finally, the study concluded by discussing managerial recommendations and providing suggestions for further studies.
Keywords: learning organization ; organizational learning ; travel agencies ; Egypt